Long-term continuous degradation of carbon nanotubes by a bacteria-driven Fenton reaction - Takahashi, Seira; Hori, Katsutoshi (Frontiers in Microbiology, 2023)
Very few bacteria are known that can degrade carbon nanotubes (CNTs), and the only known degradation mechanism is a Fenton reaction driven by Labrys sp. WJW with siderophores, which only occurs under iron-deficient conditions. No useful information is available on the degradation rates or long-term stability and continuity of the degradation reaction although several months or more are needed for CNT degradation. In this study, we investigated long-term continuous degradation of oxidized (carboxylated) single-walled CNTs (O-SWCNTs) using bacteria of the genus Shewanella. These bacteria are widely present in the environment and can drive the Fenton reaction by alternating anaerobic-aerobic growth conditions under more general environmental conditions. We first examined the effect of O-SWCNTs on the growth of S. oneidensis MR-1, and it was revealed that O-SWCNTs promote growth up to 30 μg/mL but inhibit growth at 40 μg/mL and above. Then, S. oneidensis MR-1 was subjected to incubation cycles consisting of 21-h anaerobic and 3-h aerobic periods in the presence of 30 μg/mL O-SWCNTs and 10 mM Fe(III) citrate. We determined key factors that help prolong the bacteria-driven Fenton reaction and finally achieved long-term continuous degradation of O-SWCNTs over 90 d. By maintaining a near neutral pH and replenishing Fe(III) citrate at 60 d, a degraded fraction of 56.3% was reached. S. oneidensis MR-1 produces Fe(II) from Fe(III) citrate, a final electron acceptor for anaerobic respiration during the anaerobic period. Then, ·OH is generated through the Fenton reaction by Fe(II) and H2O2 produced by MR-1 during the aerobic period. ·OH was responsible for O-SWCNT degradation, which was inhibited by scavengers of H2O2 and ·OH. Raman spectroscopy and X-ray photoelectron spectroscopy showed that the graphitic structure in O-SWCNTs was oxidized, and electron microscopy showed that long CNT fibers initially aggregated and became short and isolated during degradation. Since Shewanella spp. and iron are ubiquitous in the environment, this study suggests that a Fenton reaction driven by this genus is applicable to the degradation of CNTs under a wide range of conditions and will help researchers develop novel methods for waste treatment and environmental bioremediation against CNTs.